Event Modification in EFL Learners’ Narration: A Case Study on Retelling Alibaba Story - Pandia, Betharia Sembiring; Sibarani, Berlin (JAMI: Jurnal Ahli Muda Indonesia, 2024)
Experiences of events of both direct and vicarious ones are perceived, organized, sequenced and represented in narrative text in coherent structure. An event consist of character, action and setting. The representation of the events in narration is realized in narrative discourse. The coherent text structure is used to narrate sequence of events in various discourse strategies. This structure is also used to understand a narrative texts. Narratives comprises of constituents and supplementary events. The constituent events are causal in the sense that earlier event contributes to the occurrence of the next event that keep the story moving forward. The supplementary events are not causal; they can be removed without disturbing continuance of the story. Supplementary events are responsible for the meaning and impact of the story. If the supplementary events are removed, the meaning and impact of the story decreases. This background leads the research to investigate event modification and find out narrative discourse used to convey the story. To collect the data, the students were assigned to listen to the story of Alibaba with forty thieves, having listened to the story, they are assigned to modify the story, and retold the modified story in written form. The data were analyzed by comparing the original and the modified story based on every aspect of story structure. The results show that the students’ story modification is limited to the modification of characters and supplementary events; constituent events and narrative discourse are retained; no modification was done to the two aspects. This leads to the conclusion that sequences of events are organized, understood and produced in a coherent structure.